Evaluation of postoperative pain scores following ultrasound guided transversus abdominis plane block versus local infiltration following day surgery laparoscopic cholecystectomy-retrospective study - Vasanth Rao Kadam; Stuart Howell; V Kadam (Wolters Kluwer Medknow Publications, 2016)
Background and Aims: Postoperative pain for day surgery laparoscopic cholecystectomy has traditionally been managed with the surgeon infiltrating the wound with local anesthetic (LA). However, transversus abdominis plane (TAP) block has recently been used, although its superiority over LA remains uncertain. The primary aim was to compare LA and TAP block pain scores and analgesia used. The secondary aim was to assess satisfaction score and cost. Material and Methods: This retrospective study was commenced after ethics committee approval and ANZ clinical trial registry (ACTRN: 12612000737831). The data were collected from the theatre database and medical records of patients presenting for day case laparoscopic cholecystectomy. The sample included patients who received either bilateral port site LA infiltration with 20 ml of 0.25% Bupivacaine or bilateral TAP block with 20 ml of 0.5% ropivacaine and fentanyl postoperative pain protocol. The patients with incomplete medical records were excluded as were those admitted to an inpatient ward. Demographics and clinical characteristics were obtained from the hospital record along with pain score and postsurgery analgesia use. Postoperative pain satisfaction scores were collected by telephonic interview 30-180 days postsurgery. Results: Of 51 patients analyzed, 19 were in TAP group 29 in LA group. There were no significant differences between the LA and TAP groups with respect to postoperative pain scores (P = 0.31) or patient satisfaction scores (1 and 2+) (P = 0.36). However, fentanyl consumption in the recovery room was significantly lower in TAP group (P = 0.0079.). The consumables cost were >3 times higher in the TAP when compared to LA group. Conclusion: The performance of the TAP block with respect to pain management was comparable to LA. However, LA remains more cost effective.